Marx topology dc-dc buck converter for high voltage gain achievement - Abdirahman Ali, Fadumo (2022)
This study present Marx topology DC-DC buck converter (MBC) with a series connection at the input side and parallel connection at the output side. With these circuit configurations the high voltage gain can be achieved. In Marx topology buck mode, stages capacitor was charged in series and discharge in parallel to achieve the step-down buck characteristic. Due to the number of stages n, the buck ratio can be achieved by changing the duty cycle D, the number of circuit stages n or both. A two- stage MBC with a duty cycle of 19.4% between the input and output voltages were designed and simulated for 400 V and 48 V. Further test with duty cycle of 15.1% where the input and output are 400 V and 36 V, and duty cycle of 23.1% where the input and output are 400 V and 60 V. Simulation of output power of 1 kW, 2.5 kW and 5 kW were conducted to check the relation of the circuit towards the efficiency, output voltage and duty ratio. Simulation of switching frequency at 25 kHz, 50 kHz and 75 kHz to check the relation towards circuit parameters design. Simulation with duty cycles of 15.1%, 19.4% and 23.1% were conducted to check the relationship for the output voltage. The MBC circuit can perform the buck operation by varying the duty cycle and the number of stages for the desired output voltage. Therefore, the design of the proposed converter was confirmed. The maximum efficiency of MBC is 95% was obtained from the simulation result.